Assessment of knowledge, attitude & perception among hospital pharmacists regarding Halal pharmaceuticals - Saleha Sadeeqa,Azmi Sarriff (Journal of Applied Pharmaceutical Science, 2014)
This study aimed to assess the knowledge, attitude and perception (KAP) relating to Halal pharmaceuticals among pharmacists working in various hospitals of Malaysia. This was a cross-sectional study, carried out in the period of January 2013 to March 2013, using a structured, self-administered questionnaire. Data was collected by distributing questionnaires through respective chief pharmacists in various government hospitals in Malaysia. Study was conducted on a total of 135 pharmacists. Descriptive statistics (mean, standard deviation, frequency, percentage, median, inter quartile range) was applied to summarize the data. Chi-square Test and Fisher’s Exact Test was applied to assess the association between demographic characteristics and knowledge, attitude and perception scores. Results revealed that the hospital pharmacist had a good knowledge and positive attitude and perception about Halal pharmaceuticals. Mean knowledge, attitude and perception score was 8.01 ±1.48, 33.21± 5.66 and 51.19 ±6.49 out of maximum possible 9, 45 and 60 respectively. Mean overall KAP score out of maximum possible 114 was 92.40 ± 11.20. There was a significant, positive, and weak correlation (0.1-0.3) between knowledge and perception (r=.271, p=.001), knowledge and attitude (r=.252, p=.003) & moderate correlation (0.3-0.7) between attitude and perception (r=.542, p
Keywords: Knowledge,Attitude,Perception,Halal,Pharmaceuticals.